ANALISIS KOMPARATIF KUALITAS PELAYANAN PADA JASA PENGIRIMAN JNE EXPRESS DAN J&T EXPRESS DI INDONESIA - Nabila Nugraheni; AMA Suyanto (Universitas Muhammadiyah Kendari, 2021)
The growth of delivery services sector in Indonesia continues to grow every year. JNE Express and J&T Express are two major delivery services companies in Indonesia. To be able to survive in the intense competition of delivery service companies, companies need to implement the best service quality to consumers. Delivery services that have good service quality will certainly be more attract to consumers. This study is a comparative analysis which aims to describe the differences in service quality of JNE Express and J&T Express. The data in this study used primary data collected through questionnaires to 400 respondents. Research instrument used is five dimensions of service quality based on SERVQUAL Model and used Mann Whitney U-Test for data analysis technique. The results of descriptive analysis shows that service quality of J&T Express gets higher average than JNE Express. Based on the results of Mann Whitney U-Test shows that there are differences in reliability, responsiveness, and assurance dimensions. But, there are no difference in tangible and empathy dimensions. It can be concluded that there are differences in the service quality of JNE Express and J&T Express delivery service in Indonesia.